Meta‐analysis of antecolic versus retrocolic gastric reconstruction after a pylorus‐preserving pancreatoduodenectomy. Issue 3 (March 2015) - Bell, Richard; Pandanaboyana, Sanjay; Shah, Nehal; Bartlett, Adam; Windsor, John A.; Smith, Andrew M.
Abstract: Introduction: Delayed gastric emptying (DGE) is a common complication after a pylorus‐preserving pancreatoduodenectomy (PPPD) and is associated with significant morbidity. This study determines whether DGE is affected by antecolic (AC) or retrocolic (RC) reconstruction after a PPPD. Method: An electronic search was performed of the MEDLINE, EMBASE and PubMed databases to identify all articles related to this topic. Pooled risk ratios (RR) were calculated for categorical outcomes, and mean differences (MD) for secondary continuous outcomes using the fixed‐effects and random‐effects models for meta‐analysis. Results: Nine studies including 878 patients met the inclusion criteria. DGE was lower with an AC reconstruction RR 0.31 [0.12, 0.78] Z = 2.47 ( P = 0.010). Length of stay (LOS) MD −4 days [−7.63, −1.14] Z = 2.65 ( P = 0.008) and days to commence a solid diet MD −5 days [−6.63, −3.15] Z = 5.50 ( P ≤ 0.000) were also significantly in favour of the AC group. There was no difference in the incidence of pancreatic fistula, intra‐abdominal collection/bile leak or mortality between the two groups. Conclusion: AC reconstruction after PPPD is associated with a lower incidence of DGE. Time to oral intake was significantly shorter with AC reconstruction, with a reduced hospital stay.